2020
DOI: 10.14295/transportes.v28i3.1954
|View full text |Cite
|
Sign up to set email alerts
|

Análise da implementação de mistura asfáltica com granulometria do tipo descontínua para redução de acidentes em pista molhada

Abstract: Acidentes de trânsito são eventos complexos envolvendo múltiplas causas, geralmente conectados a falhas humanas relativas à interpretação do ambiente da via onde trafegam. Tais eventos causam perdas de vidas, além de prejuízos sociais e econômicos. Neste contexto, é essencial para a gestão de rodovias a execução de projetos que minimizem tais erros. Dentre os fatores mais estudados para reduzir acidentes encontra-se a infraestrutura viária, principalmente no que tange à geometria, à sinalização e às condições … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Although binders modi ed with rubber improve the behavior of asphalt mixtures in general, Venudhara et al (2017) have found in various studies that discontinuous grades, such as gap graded, are more suitable for producing rubberized mixtures, and their behavior characteristics are signi cantly improved compared to conventional mixtures. Other authors have also analyzed the results of gap grading rubberized asphalt in the eld ( Van Kirk, 1997;Raad et al, 2001;Huang et al, 2002;Zborowski et al, 2004;Fontes et al, 2010;Zeiada et al, 2012;Chiu, 2008;Losa et al, 2012;Said et al, 2015;Carvalho et al, 2020;Buttlar & Rath, 2021, Nair & Hossain, 2022. In general, the behavior of these experimental sections carried out in different parts of the world indicated that the rubber gap mixtures showed a notable improvement in the behavior of asphalt paving in different tra c situations and environmental conditions compared to conventional asphalt binders.…”
Section: Introductionmentioning
confidence: 99%
“…Although binders modi ed with rubber improve the behavior of asphalt mixtures in general, Venudhara et al (2017) have found in various studies that discontinuous grades, such as gap graded, are more suitable for producing rubberized mixtures, and their behavior characteristics are signi cantly improved compared to conventional mixtures. Other authors have also analyzed the results of gap grading rubberized asphalt in the eld ( Van Kirk, 1997;Raad et al, 2001;Huang et al, 2002;Zborowski et al, 2004;Fontes et al, 2010;Zeiada et al, 2012;Chiu, 2008;Losa et al, 2012;Said et al, 2015;Carvalho et al, 2020;Buttlar & Rath, 2021, Nair & Hossain, 2022. In general, the behavior of these experimental sections carried out in different parts of the world indicated that the rubber gap mixtures showed a notable improvement in the behavior of asphalt paving in different tra c situations and environmental conditions compared to conventional asphalt binders.…”
Section: Introductionmentioning
confidence: 99%